Assessment of indications of caesarean section among high risk women by Robson criteria: a prospective study - Patel, Kaveri Shaw; Nag, Roma S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Caesarean section (CS) is a surgical intervention for safe delivery other than natural vaginal route. World Health Organization (WHO) has recommended ten group classification systems of Robson criteria which we have used to analyse CS at our center. The objective of the study to analyse the lower section caesarian section (LSCS) data under Robson criteria for implementation in regular practice in tertiary care center and to understand the need of it for future practice. Methods: A prospective analysis done for deliveries in Obstetric Department of Shalby Multispecialty Hospital of central India by Robson ten group classification criteria. The study was carried out for the period of two year from April 2016 to April 2018 including antenatal women attending labour room with high risks or referred cases from other centers. Results: The study reflected overall 196 live birth of high risk cases which were having other co morbidities like pre-eclampsia, eclampsia, hypothyroidism, diabetes, acute viral hepatitis. The data compared with Robsons guidelines and reflected that the centre is dealing with high risk primigravida (47.51%, 35-42% Robson criteria) cases with high CS rate (16.8%, group 5). There was multiple pregnancy, group 8, (2.32 %, >1.5-2% Robson Criteria) and preterm births as in group 10, 18.02 % (5% in Robson Criteria), exclusively high. Conclusions: The Robson criteria help to classify the population handled by the canter to develop the strategies for betterment of services. It has limitation in view of qualitative assessment of the data for comorbidities and severity of the disease.